STRESS ANALYSIS PADA HORIZONTAL AXIS WIND TURBINE BLADE - Achmad Rachmad Tullah; Made K Dhiputra; G Soeharsono (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: Nowadays wind turbine is used widely in many countries as power plant. When the wind turbine blade rotates there will be aerodynamic forces acting on the blade such as drag, lift, weight and centrifugal forces. When designing wind turbine blade it is necessary to test whether the blade can withstand the aerodynamic forces or not. Stress analysis is a feature that can predict stress acting on construction. Nowadays there are many stress analysis softwares that can be used to predict stress. In this research the stress analysis will be used by using autodesk inventor.The research purposes are to find the stress acting on the wind turbine blade and to get the maximum stress location.